Payout Policy, Capital Structure, and Compensation Contracts when Managers Value Control - Chang, Chun (Review of Financial Studies, 1993)
[The optimal contract between managers and investors is endogenously derived when managers have preferences for both monetary compensation and corporate resources under their control. When the optimal payout is privately known to managers, they can be induced to make payouts by linking their compensation to the payout. Public equity is a claim on this discretionary payout. If investors can obtain new information about the firm's optimal payout level, it can be utilized by transferring the control from management to investors. The new information allows the firm to achieve a more efficient allocation through recontracting. We show that the new information will be obtained if and only if the payout falls below a promised level.]